Metabolic Engineering Strategies in Diatoms Reveal Unique Phenotypes and Genetic Configurations With Implications for Algal Genetics and Synthetic Biology - George, Jestin; Kahlke, Tim; Abbriano, Raffaela M.; Kuzhiumparambil, Unnikrishnan; Ralph, Peter J.; Fabris, Michele (Frontiers in Bioengineering and Biotechnology, 2020)
Diatoms are photosynthetic microeukaryotes that dominate phytoplankton populations and have increasing applicability in biotechnology. Uncovering their complex biology and elevating strains to commercial standards depends heavily on robust genetic engineering tools. However, engineering microalgal genomes predominantly relies on random integration of transgenes into nuclear DNA, often resulting in detrimental “position-effects” such as transgene silencing, integration into transcriptionally-inactive regions, and endogenous sequence disruption. With the recent development of extrachromosomal transgene expression via independent episomes, it is timely to investigate both strategies at the phenotypic and genomic level. Here, we engineered the model diatom Phaeodactylum tricornutum to produce the high-value heterologous monoterpenoid geraniol, which, besides applications as fragrance and insect repellent, is a key intermediate of high-value pharmaceuticals. Using high-throughput phenotyping we confirmed the suitability of episomes for synthetic biology applications and identified superior geraniol-yielding strains following random integration. We used third generation long-read sequencing technology to generate a complete analysis of all integration events, genomic locations, and transgene arrangements associated with high-performing strains at a genome-wide scale with subchromosomal detail, never before reported in any microalga. This revealed very large, highly concatenated insertion islands, offering profound implications on diatom functional genetics and next generation genome editing technologies, and are key for developing more precise genome engineering approaches in diatoms, including possible genomic safe harbour locations to support high transgene expression for targeted integration approaches. Furthermore, we have demonstrated that exogenous DNA is not integrated inadvertently into the nuclear genome of extrachromosomal-expression clones, an important characterisation of this novel engineering approach that paves the road to synthetic biology applications.